Mental Health Resilience Among Santri: A Salutogenic Perspective on Psychological Well-Being in Pesantren: A Salutogenic Perspective on Psychological Well-Being in Pesantren - Ratodi, Muhamad; Zubaidah, Tien; Legawati; Natalina, Riny (Universitas Airlangga, 2025)
Background: Mental health is a vital although insufficiently examined component of student well-being at pondok pesantren (Islamic boarding schools). Pesantren offer organized religious instruction and discipline, although they also pose distinct psychological issues. Objective: This study examines the mental health resilience of santri at Pondok Pesantren Darussalam Martapura utilizing Antonovsky’s Salutogenic Model. Methods: A qualitative case study methodology was employed, utilizing semi-structured interviews, participant observations, and document analysis involving 40 respondents, comprising santri, ustadz, and administrators emphasizing comprehensibility, manageability, and meaningfulness as protective variables Results: The results indicate that pesantren cultivate resilience via faith-based coping mechanisms (82%), peer social support (74%), and organized routines (68%). Nonetheless, 62% of santri experience stress attributed to stringent discipline, while merely 32% have access to professional psychological services, underscoring deficiencies in mental health support. Although faith imparts a significant sense of purpose (81%), it does not entirely alleviate stress, since 43% continue to endure chronic psychological suffering. Conclusion: The research conclude that incorporating mental health education, flexible disciplinary systems, and organized counseling services within pesantren can improve resilience while upholding religious principles. These findings enhance the broader dialogue on mental health promotion within faith-based educational environments and advocate for a comprehensive approach to student well-being.